Proceso de Recuperación del Impuesto al Valor Agregado (IVA) del GAD Municipal de Babahoyo - Vera Alvarado, Arelis Susana (2018)
This case study is applied to the Municipal Autonomous Decentralized Government of the Babahoyo Canton, which wishes to follow up on the problems the institution maintains in the process of refunding the Value Added Tax, because it takes a long time to receive said values ​​that by law All VAT that is paid to the suppliers is returned by the state through the Ministry of Finance. Before focusing on the VAT refund process it is important to mention that the right that the Municipalities have in the refund of VAT by the State is a right that is established in the constitution of the country and it is the duty of the officials to demand that its officials comply with this right. (BOHLANDER, 2015) The public institution object of the case study is the Municipal Autonomous Decentralized Government of the Babahoyo canton, which is located in Av. General Barahona and 27 de Mayo (corner), is an entity that is subject to internal problems that are affecting the availability of funds, due to the inconveniences presented by the VAT refund processes carried out in the Financial Department. The lack of knowledge and the non-segregation of an official that is specifically responsible for this process lead to the GAD. Municipal de Babahoyo, do not request the refund of the Value Added Tax, a period that the Law authorizes to request it.